Possibility of the use of data of infrasonic monitoring for identification of the nature of seismic events - A. Lyashchuk; Yu. Andrushchenko; Yu. Gordienko; E. Karyagin; I. Kornienko (Геофизический журнал, 2015)
The paper considers the possibility of the use of infrasound measurements conducted in Ukraine to verify the recorded seismic events and the use of infrasound data as one of the criteria for their identification. Registration of seismic and infrasonic signals was carried out via a network of geophysical Main center of special monitoring. To register infrasound small-aperture infrasound arrays were used, allowing directional monitoring of events. The data of 909 parameters of seismic events from industrial explosions that occurred during 2014 in Ukraine have been obtained. 124 infrasonic responses on these events have been registered. The limits of sensitivity and distance of the use of infrasound method have been found. The proposed technology of registering signals from seismic events by seismic-acoustic complex makes possible to register surface industrial explosions at a distance of 200 kilometers.